Dr Mahathir predicts election won't be too long from now - New Sabah Times English, (KK) (New Sabah Times English (KK), 2012)
SINTOK: Former Prime Minister, Tun Dr Mahathir Mohamad said yesterday he said feels that the 13th general election will be held soon as the situation "looks good" for the ruling coalition.